PEMANFAATAN MEDIA SOSIAL OLEH MAHASISWA SISTEM INFORMASI UNTUK MENUMBUHKAN NASIONALISME DI ERA DIGITA - Arribe, Edo; Fauzan, Wahyu; Abdussalam, Rafiq; Fazilla, Rahma Muti; Pratama, Dzaky Medlin (Communication Science Department - Faculty of Social and Political Sciences, Universitas Satya Negara Indonesia (USNI), 2025)
The development of digital technology has shifted how young people express national identity, especially among students. This study aims to examine how Information Systems students at Universitas Muhammadiyah Riau use social media, particularly TikTok, to promote nationalism. A qualitative, descriptive-exploratory approach was used, with data collected through observation, interviews, open questionnaires, and documentation. The findings indicate that students are not just consumers but also creators of nationalistic content on social media. They express national pride through local culture content, patriotic hashtags, and historical commemorations. Influencing factors include digital literacy, social environment, global culture, and institutional support. The study concludes that social media plays a strategic role in forming digital nationalism that is adaptive, symbolic, and relevant for the youth in the digital age.